Expo 86, Vancouver, B.C., Canada - Jurgen Vogt/Photo Graphics::::::::: (Agency Press)
The Land Plaza features an international traffic jam celebrating the World's most colorful modes of transportation from beast of burden to 18 wheel trucks.